2006
DOI: 10.1097/01.qco.0000224825.57976.87
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal infection and long-term neurodevelopmental outcome in the preterm infant

Abstract: Enhanced understanding of the interaction of infection, inflammation and brain injury will be critical to developing strategies to improve neurodevelopmental outcome in preterm infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
176
0
8

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 312 publications
(187 citation statements)
references
References 60 publications
3
176
0
8
Order By: Relevance
“…Moreover, clinical, histological, and experimental data on diseases exclusively manifesting during the neonatal period, such as bronchopulmonary dysplasia (3,6,31) and periventricular leukomalacia (4,7,32), are all linked to prolonged inflammation leading to tissue destruction. Thus, the data presented here might contribute to a molecular explanation for the "sustained inflammation" seen in neonates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, clinical, histological, and experimental data on diseases exclusively manifesting during the neonatal period, such as bronchopulmonary dysplasia (3,6,31) and periventricular leukomalacia (4,7,32), are all linked to prolonged inflammation leading to tissue destruction. Thus, the data presented here might contribute to a molecular explanation for the "sustained inflammation" seen in neonates.…”
Section: Discussionmentioning
confidence: 99%
“…Although acute bacterial infection can be controlled in many cases, the accompanying inflammatory reaction, sometimes starting before birth, may be excessive and hardly controllable (3). Inflammation may even persist after resolution of infection, because sepsis predisposes to inflammatory diseases exclusively manifesting during the neonatal period, i.e., bronchopulmonary dysplasia and periventricular leukomalacia (2,(4)(5)(6)(7). As for this, Dammann et al coined the term "sustained inflammation" to describe a prolonged inflammatory reaction after an initial activation of the neonatal immune system, with an inability to resolve the resultant inflammation (8,9).…”
mentioning
confidence: 99%
“…3,[7][8][9][10] Preterm infants, known to exhibit a markedly increased risk for the development of severe infections, may critically depend on their innate immune response, as the presence of early-onset and nosocomial infections mainly determines acute and long-term morbidity and mortality in this population, especially regarding the development of neurological and pulmonary impairment. [17][18][19] Especially, the development of chronic lung disease in preterm infants is known to be triggered by infectious complications and ongoing inflammatory processes. 18,[20][21][22] The aim of the present study therefore was to investigate whether genetic variation within the MBL gene is associated with alterations of acute and long-term pulmonary morbidity in preterm infants.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to respond effectively to infectious hazards clearly determines acute and long-term outcome especially in preterm infants. [17][18][19] Thus, several studies revealed pre-and postnatal infections to contribute to the development of chronic lung disease in preterm infants, 18,[20][21][22] which mainly determines morbidity and mortality during the first year of life in this patient cohort. Bronchopulmonary dysplasia (BPD) is histologically characterized by decreased alveolar septation resulting in large saccular airspaces, representing a rupture of pulmonary development from the saccular to the alveolar stage.…”
Section: Introductionmentioning
confidence: 99%
“…A reduction in the incidence and impact of sepsis in very premature neonates is important, especially in light of the devastating sequelae associated with neonatal infection. 5,6 Intravenous immunoglobulin administration in neonates has been aimed at treatment of sepsis and prophylaxis to reduce the incidence of sepsis. Regarding the use of IVIg as a treatment for sepsis, a Cochrane meta-analysis showed a reduction in mortality of neonates treated with IVIg for what were subsequently proven infections (RR 0.55 (95% CI, 0.31-0.98)).…”
Section: Introductionmentioning
confidence: 99%